Governor vessel moxibustion for cancer-related fatigue in colorectal patients: a randomized trial - Li, Huakang; Huang, Wei; Du, Kangming; Liu, Wei; Wu, Ziliang; Xu, Bo; Li, Qiang; Wang, Yue; Lin, Bing (Frontiers in Oncology, 2023)
Abstract Objective: This study aimed to investigate the efficacy and mechanism of action of Governor Vessel Moxibustion (GVM) in the treatment of Cancer-Related Fatigue (CRF) in patients who have completed treatment for colorectal cancer. Methods: We randomly assigned 80 CRF patients in a 1:1 ratio to either the experimental group or the control group. During the three-week treatment period, both groups of patients received usual care for CRF provided by professional nurses. The experimental group received additional GVM treatment (three times a week, nine times total). The primary outcome was the mean change in total fatigue score from baseline to the end of treatment, assessed using the Chinese version of the Piper Fatigue Scale. Results: At baseline, the total fatigue scores were 6.20±0.12 in the experimental group and 6.16±0.14 in the control group. At the end of treatment, the total fatigue scores decreased by 2.03 points (32.7% decrease from baseline) in the experimental group and by 0.99 points (15.6% decrease from baseline) in the control group. The absolute reduction in total fatigue scores in the experimental group was 1.04 points higher than in the control group (95% CI, 0.93 to 1.15; P<0.001), corresponding to a relative difference of 17.1% (95% CI, 15.2% to 18.9%; P<0.001). At the end of treatment, the experimental group showed greater reductions in interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) levels compared to the control group. No serious adverse events related to GVM treatment were observed. Conclusion: GVM appears to be safe and effective for alleviating CRF in patients who have completed colorectal cancer treatment, which may be related to the modulation of IL-6 and TNF-α levels.